LU-HF AND AR-AR CHRONOMETRY SUPPORTS EXTREME RATE OF SUBDUCTION ZONE METAMORPHISM DEDUCED FROM GEOSPEEDOMETRY - Philippot P.; Perchuk A.L.; Blichert-Toft J.; Gerasimov V.; Costa S. (My University, 2001)
Recent diffusion modeling of eclogitic garnets from the Great Caucasus, Russia, and Yukon, Canada, have shown that the preservation of garnet growth zoning in rocks that have equilibrated at high temperature (680–700 °C) is possible only if rates of pressure and temperature change on the burial and/or exhumation paths are in the order of several cm/year and several hundreds of °C/Ma. In order to confirm this observation, we performed Lu–Hf and Sm–Nd dating of garnet and Ar–Ar dating of mica on the same samples that were used for geospeedometry measurements in an earlier study. In both localities, garnet grew during prograde metamorphism at 690±40 °C and >1.5 GPa (Yukon) and 680±40 °C and >1.6 GPa (Great Caucasus). In contrast, phengite formed soon after the main eclogitic foliation at 520±50 °C (Yukon) and 600±40 °C (Great Caucasus).